THE INFLUENCE OF COMMUNITY SOCIAL CLASS ON THE ATTITUDES TO LEARNING SCIENCES IN HIGH CLASS STUDENTS OF SDN 1 GRANTING JOGONALAN KLATEN - Lily Ekawati (Universitas Sebelas Maret, 2022)
A good social attitude teaches students how to behave with the surrounding environment, which includes family, teachers, society, and friends. The object of social attitudes is human social life both in the family, school, and community (Sanjiwana, Pudjawan, & Margunayasa, 2015). Social attitudes make students accustomed to fostering honesty, responsibility, care for others, tolerance, cooperation, discipline, courtesy, and self-confidence. This study aims to determine the effect of community social class on social studies learning attitudes in high school students of SDN 1 Granting Jogonalan Klaten in the 2021/2022 school year. The population and research samples were 4th, 5th and 6th grade students of SDN 1 Granting Jogonalan Klaten, and the total sample was 65 students. The data collection method used questionnaires and documentation. Technical data analysis using simple linear regression. Based on the results described in table 3, it is known that 3.33% or as many as 1 student has a poor attitude of tolerance with a value calculation of 43.76-62.50. Then as many as 33.3% or 10 students have a good attitude of tolerance with a value calculation range of 62.51 -81.25. The remaining 63.3% or as many as 19 students have a very good attitude of tolerance with a value calculation range between 81.26 -100.